2015
DOI: 10.1080/19338244.2015.1116429
|View full text |Cite
|
Sign up to set email alerts
|

Association of various risk factors with chronic lymphocytic leukemia and its cytogenetic characteristics

Abstract: This study aimed to investigate whether occupational and environmental exposures, lifestyle, family, and medical history are associated with chronic lymphocytic leukemia (CLL) risk and its chromosomal abnormalities. The study included 138 CLL cases and 141 age- and sex-matched controls. Information data were collected through in-person interviews from cases and controls. Cytogenetic analysis was performed on CLL bone marrow cells. Positive associations were found between CLL and cancer family history, smoking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Additionally, the inclusion of more studies allowed for the further investigation of exposure characteristics, including hair dye type and duration/time period of use. A methodological limitation was less accurate exposure classification in studies that assessed the risk of leukemia due to a suite of past occupational and lifestyle exposures, and therefore only collected limited data on the history of lifetime hair dye use . Specifically, studies that only collected information on “ever” use of hair dye were unable to adequately characterize exposure profiles that may influence the risk of disease, as shown in the above stratified analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the inclusion of more studies allowed for the further investigation of exposure characteristics, including hair dye type and duration/time period of use. A methodological limitation was less accurate exposure classification in studies that assessed the risk of leukemia due to a suite of past occupational and lifestyle exposures, and therefore only collected limited data on the history of lifetime hair dye use . Specifically, studies that only collected information on “ever” use of hair dye were unable to adequately characterize exposure profiles that may influence the risk of disease, as shown in the above stratified analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Since the meta‐analysis of Takkouche in 2005, ten studies have been published in which the association between personal hair dye use and the risk of one or more leukemia subtypes was evaluated . Many of these more recent studies provided more robust information on gender and hair dye use patterns, including hair dye type and time period/duration of use.…”
Section: Introductionmentioning
confidence: 99%
“…Lachapelle (1986) Possick et al (1970) Sertoli et al (1992 Skotnicki-Grant (2008) Focus groupsInterviews with workers exposed to insulation materials that contain some mention of the role of larger diameter fibers. Adegoke et al, 2003: Brown et al, 1990Costantini et al, 2008;Deschler & L€ ubbert, 2006;Glass et al, 2003;IARC, 2012;Rinsky, 1989;Rodriguez-Abreu et al, 2007;Schwilk et al, 2010;Smith & Zhang, 1998;Zeeb & Blettner, 1998;Zhang et al, 2009Electromagnetic fields Floderus et al, 1993Karakosta et al, 2016;Rodriguez-Abreu et al, 2007Radiation Band et al, 1996Deschler & L€ ubbert, 2006;Greaves, 1997;Karakosta et al, 2016;Leuraud et al, 2015;Richardson et al, 2015;Rodriguez-Abreu et al, 2007;Smith & Zhang, 1998;Zeeb & Blettner, 1998Lifestyle-related Smoking Brownson et al, 1993Danaei et al, 2005;Fernberg et al, 2007;Fircanis et al, 2014;Kane et al, 1999;Karakosta et al, 2016;Smith & Zhang, 1998;Wang et al, 2015Obesity Calle et al, 2...…”
Section: Appendixmentioning
confidence: 99%
“…Matsuoka & Jeang, 2007;De Roos et al, 2013;Rodriguez-Abreu et al, 2007 Family history Family history of leukemia or any cancer. Karakosta et al, 2016;Rauscher et al, 2002 (a) Some reported associations are controversial, such as the relation between occupational exposure to formaldehyde and leukemia (Collins & Lineker, 2004;Heck and Casanova, 2004). (b) IARC (2012) concluded that there is limited human evidence for the carcinogenicity of ethylene oxide.…”
Section: Appendixmentioning
confidence: 99%
“…39 ). CLL occurrence has also been connected with several occupational and environmental exposures 37,40 . Among first-degree relatives of CLL patients, there is an increased risk of the same malignancy or other lymphoproliferative diseases 37,[41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%